2007
DOI: 10.1128/jb.00179-07
|View full text |Cite
|
Sign up to set email alerts
|

A Large Gene Cluster in Burkholderia xenovorans Encoding Abietane Diterpenoid Catabolism

Abstract: Abietane diterpenoids are defense compounds synthesized by trees that are abundant in natural environments and occur as significant pollutants from pulp and paper production. Burkholderia xenovorans LB400 has diverse catabolic capabilities and represents an important group of heterotrophic bacteria in soil environments. The genome sequence of LB400 revealed homologs of the dit genes of Pseudomonas abietaniphila BKME-9, which encode abietane diterpenoid degradation. LB400 grew on abietic acid (AbA), dehydroabie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 36 publications
3
46
0
Order By: Relevance
“…The ortholog of PA2G 02002 in P. abietaniphila is DitE (absent in B. xenovorans). PA2G 02028 shares significant similarity (57%) with B. xenovorans Bxe C0645 whose expression was shown to be induced by growth of the bacteria on dehydroabeitic acid (25).…”
Section: Evolution Of Rgp29 In Strain Pa2192 and Acquisition Of New Mmentioning
confidence: 97%
See 1 more Smart Citation
“…The ortholog of PA2G 02002 in P. abietaniphila is DitE (absent in B. xenovorans). PA2G 02028 shares significant similarity (57%) with B. xenovorans Bxe C0645 whose expression was shown to be induced by growth of the bacteria on dehydroabeitic acid (25).…”
Section: Evolution Of Rgp29 In Strain Pa2192 and Acquisition Of New Mmentioning
confidence: 97%
“…12). These compounds are synthesized by trees as defense molecules and several bacteria, including Pseudomonas abietaniphila and Burkholderia xenovorans, can use abietane diterpenoids as the sole carbon source (24,25). Twenty-three of the P. aeruginosa dit genes (PA2G 01983 to PA2G 02008) are highly homologous to genes in P. abietaniphila BKME-9 (62-91% sequence identity of their protein products) with conserved synteny (26).…”
Section: Evolution Of Rgp29 In Strain Pa2192 and Acquisition Of New Mmentioning
confidence: 99%
“…Gene replacement. The gene encoding DitQ and the gene encoding DitU were disrupted by replacement as previously described (38). The primers and plasmids used are listed in Tables 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
“…The possible presence of functional P450 homologs with complementary activities may explain how the P450 knockout strains described above retained a capacity for reduced growth on abietanes. However, transcriptomic analysis of LB400 indicated that ditQ, but not ditU, was up-regulated during growth of LB400 on DhA (38). Thus, the patterns of expression and substrate specificities of various P450s likely dictate distinct roles for the enzymes in abietane metabolism, and these roles remain to be elucidated.…”
mentioning
confidence: 99%
See 1 more Smart Citation